2013
DOI: 10.7439/ijpc.v2i4.755
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Potent Antitubercular Agent Isoniazid and Its Analogues

Abstract: ABSTRACT:There has been considerable interest in the development of new anti tubercular agents particularly against multidrug resistance and extensively drug resistant strain of tuberculosis because mycobacterium species have developed resistant against currently used drugs. The currently use antitubercular drugs having toxic effect and long period of therapeutic treatment. Therefore, many researchers have synthesized various newer drugs and analogues of currently used drugs for tuberculosis treatment. These o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…Pyridazin‐3(2 H )‐one derivatives constitute an interesting class of heterocyclic lead compounds for drug discovery and research into anticancer molecules . Recently, it was reported that some pyridazin‐3(2 H )‐one derivatives specifically interact with and inhibit PIM (potential tumor targets) kinases with low nanomolar potency . In addition, pyridazin‐3(2 H )‐ones are endowed with many biological activities .…”
Section: Introductionmentioning
confidence: 99%
“…Pyridazin‐3(2 H )‐one derivatives constitute an interesting class of heterocyclic lead compounds for drug discovery and research into anticancer molecules . Recently, it was reported that some pyridazin‐3(2 H )‐one derivatives specifically interact with and inhibit PIM (potential tumor targets) kinases with low nanomolar potency . In addition, pyridazin‐3(2 H )‐ones are endowed with many biological activities .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, phthalazine heterocyclic derivatives have attracted attention due to their high therapeutic value in analgesic, anti-inflammatory, antimicrobial, antithrombotic, antidepressant, diuretics, antihypertensive, antitubercular, and anti-HIV treatments [22]. Flexible synthetic routes to new scaffolds for generating various drug-based phthalazines thus represent a high of priority for catalyst design [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, phthalazine heterocyclic derivatives have attracted attention due to their high therapeutic value in analgesic, anti-inflammatory, antimicrobial, antithrombotic, antidepressant, diuretics, antihypertensive, antitubercular, and anti-HIV treatments [22]. Flexible synthetic routes to new scaffolds for generating various drug-based phthalazines thus represent a high of priority for catalyst design [22][23][24]. In this context, previous research has focused on catalytic functions immobilized on nanoparticles [25][26][27][28][29][30], wherein the catalytic surface area is related to the particle size and shape, and is generally too low to provide high activity.…”
Section: Introductionmentioning
confidence: 99%
“…This is considered a major contributing factor to long drug treatments for TB. 12 For this reason, it is important to determine if compounds have potential activity against these bacteria at the onset of design. The physicochemical properties were also studied that directly affect the pharmacokinetics and pharmacodynamics of drugs.…”
Section: Rational Drug Designmentioning
confidence: 99%
“…Compounds missing N--oxide groups have led to the loss of anti--TB activity. Over 500 derivatives of quinoxaline (12) were studied and it clearly demonstrated the importance of this group for developing a new class of anti--TB compounds. The quinoxaline compounds have activity on non--replicating bacteria, which could lead to shorter anti--TB activity.…”
Section: Non--fluoroquinolonesmentioning
confidence: 99%